Enhancing Halal Certification Compliance Among MSMEs Through Asset-Based Community Development: Evidence from Coastal Tourism in Indonesia - Heru Juabdin Sada; Yudesta Erfayliana; Muhammad Aridan; Muhammad Sufian; Faridha Noer Barkah (Smart Society, 2026)
The implementation of mandatory halal certification policies in Indonesia presents significant challenges for micro, small, and medium enterprises (MSMEs), particularly in tourism-driven coastal areas where regulatory literacy and procedural readiness remain uneven. This study aims to examine whether an Asset-Based Community Development (ABCD) approach can enhance halal certification readiness among MSME actors operating in Pahawang Beach and Klara Beach, Lampung Province. Employing a quasi-experimental pretest–posttest design combined with qualitative triangulation, data were collected from 50 MSME participants through structured surveys, focus group discussions, and field observations. The intervention focused on strengthening regulatory awareness, procedural literacy, attitudinal readiness, and behavioral commitment toward halal certification. The findings indicate substantial improvements across knowledge and compliance indicators, including increased understanding of legal obligations, certification timelines, and administrative sanctions, as well as a marked rise in certification registration interest and application behavior. The results further reveal that prior barriers were predominantly procedural rather than ideological, and that participatory mentoring effectively reduced informational asymmetry while activating community-level support networks. By integrating regulatory compliance with asset-based empowerment, this study advances halal governance scholarship and demonstrates that community-driven facilitation can function as an effective intermediary mechanism between statutory mandates and MSME institutional engagement. The implications suggest that mandatory halal certification policies should be accompanied by localized participatory capacity-building strategies to ensure inclusive compliance, particularly within emerging halal tourism ecosystems.